2019
DOI: 10.1016/j.finel.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A parallel non-invasive mixed domain decomposition - Implementation and applications to mechanical assemblies

Abstract: This paper proposes to confront a mixed domain decomposition method with industrial computations, in particular the simulation of quasi-static assemblies with frictional contact between the parts. The method is implemented in a non-invasive manner around an industrial finite element software. The performance of the algorithm is studied on industrial assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Remark 4 : It may also be noticed that our method appears compatible with previous works performed regarding the parallel computation of nonlinear problems using Code_Aster (Duval et al , 2016; Oumaziz et al , 2019). As a result, the use of our strategy in combination with such works should allow the parallel computation of nonlinear IGA using Code_Aster .…”
Section: Extension To Nonlinear Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…Remark 4 : It may also be noticed that our method appears compatible with previous works performed regarding the parallel computation of nonlinear problems using Code_Aster (Duval et al , 2016; Oumaziz et al , 2019). As a result, the use of our strategy in combination with such works should allow the parallel computation of nonlinear IGA using Code_Aster .…”
Section: Extension To Nonlinear Analysissupporting
confidence: 80%
“…This appears of crucial interest regarding industrial FE environments as the access to the whole code is not needed and the FE routines that may be highly optimized are not touched. In that sense, the proposed method lies in the family of so-called non-invasive (also denoted non-intrusive ) methods that have been recently applied to local-global coupling (Gendre et al , 2009; Bouclier et al , 2016; Bouclier et al , 2017), domain decomposition (Duval et al , 2016), contact problems (Oumaziz et al , 2017; Oumaziz et al , 2019), transient dynamics analysis (Bettinotti et al , 2014) and stochastic partial differential equations (Chevreuil et al , 2013). Their ultimate goal is then to tackle real industrial applications (Guinard et al , 2018) for real aeronautical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Both search directions H and h are the parameters of the method. One can interpret h as an interface rigidity [18]. The computation of the R operator comes directly from the hosting software as a black-box.…”
Section: Kinematic Conditions and Equilibrium Equationmentioning
confidence: 99%
“…Another point lies in the management of time-dependent non-linear problems with ROM methods. In this context, the LATIN-PGD method [13,14] is a worthwhile one, which has been the subject of many works highlighting its assets: ostensible reduction of computation time [15,16], construction of virtual charts [7], ability to address all types of non-linearities [17,18] among others. Hence, the LATIN-PGD method is attractive to Siemens Digital Industries Software, as a promising tool in the Digital Twins landscape.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the one-way method drawbacks, some papers [18]- [21] propose to add a macromodel correction step in order to obtain a full iterative procedure. It was shown that the two-way method efficiently solves the generic structural mechanic problem [18], large assemblies [19], fuels [20], and nuclear reactors in [21]. However, insufficient or no interest whatsoever has so far been given to the implementation of the two-way method in multiscale modeling of power IC, for assessing the thermomechanical local plasticity.…”
Section: Introductionmentioning
confidence: 99%